MANAJEMEN SURAT MASUK, BUKU TAMU DAN DISPOSISI SURAT DENGAN APLIKASI E-OFFICE PADA BALAI TEKNOLOGI INFORMASI DAN KOMUNIKASI DINAS PENDIDIKAN PROVINSI MALUKU - Marion Erwin Dien (Politeknik Negeri Ambon, 2023)
An information system or e-office application is one of the applications developed with the aim of helping office administration management to be more effective and efficient. As one of the UPT (Technical Implementation Units) within the Maluku Provincial Government, the Education Information and Communication Technology Center develops e-office applications as a form of electronic data management. The system development method used in this study is the Waterfall Model and was developed using the Laravel Framework and MySQL database. This research was conducted with the aim of implementing an e-office application at the Tekkom Office of the Maluku Province Education Office with guest/visitor book features, incoming mail filing, letter disposition, guest/visitor book reports and incoming mail reports. With this application, office administration management such as guest book data and incoming mail can be managed electronically so that it becomes more effective and efficient.